Public Opinion of the facial recognition policy in China by Indonesian Student in Nanjing City - Fadillah, Dani (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine how perceptions of Indonesian students in the city of Nanjing of the facial recognition policy implemented by the Chinese government. A surveillance camera with facial recognition technology enables a person to be immediately identified whenever and wherever he is, especially now in China the presence of facial recognition cameras fills every corner of the city up to public vehicles. The author gets information about their perceptions by distributing questionnaires and conducting interviews with Indonesian students in the city of Nanjing, after obtaining the data and information the author needs, and then using the logic of social action theory that was coined by Max Weber. The results of this study indicate that the presence of facial recognition technology surveillance cameras affects the personality of Indonesian students in the city of Nanjing in acting, even though there are certain variables that make them actually dare to break a rule even though they realize that they are in full control..Keywords--,,